Computation of the nonlinear optical properties of n-type asymmetric triple δ-doped GaAs quantum well. (June 2019) - Ungan, F.; Pal, S.; Bahar, M.K.; Mora-Ramos, M.E.
Abstract: In the present study, we present numerical results for the influence of non-resonant intense THz laser radiation as well as the structure parameters, such as well width and central doping concentrations, on the total optical absorption coefficients (TOACs) and relative refractive index changes (RRICs) in n -type asymmetric triple δ -doped G a A s quantum well (QW) by using the compact-density-matrix formalism via iterative method. In order to obtain these numerical results, we have first obtained the subband energy spectrum and the electronic wave functions of the structure by using the effective-mass and parabolic band approximation. We have then calculated the nonlinear optical (NLO) properties of the system, by employing these energy eigenvalues and eigenfunctions. The numerical results for these calculations show that; (i) the magnitude of the resonant peak of TOACs decreases and the peak position shifts towards the lower energies when the central doping concentration and the well width are increased; (ii) due to the intense laser field effect, the magnitude of the TOACs resonant peak initially increases and its position shifts towards higher energies and then it decreases, shifting towards lower energies; (iii) by increasing the central doping concentration (well width), the magnitude of the resonant peak of RRICs increases (decreases), and the resonant peak position shifts towards the lower energies; and finally (iv) because of the increase in the intensity of the laser field applied to the structure, the magnitude of the resonant peak of RRICs increases, and the resonant peak position initially shifts towards the higher energies and then shifting towards the lower energies. Highlights: The magnitude of the TOACs decrease with the central doping concentration. The magnitude of the TOACs and RRICs decrease with the well width. The ILF have to important effects on the optical properties of n-type ATDD QW.